Ciliate protists from Cabiúnas Lagoon (Restinga de Jurubatiba, Macaé, Rio de Janeiro) with emphasis on water quality indicator species and description of Oxytricha marcili sp. n. - Paiva,T. S. (2004)
We found 34 species of ciliate protists in the samples collected by the margins of Cabiúnas Lagoon during 2001. The ciliates were cultivated in the laboratory, where they were examined in vivo and identified through silver impregnation techniques. A new species, Oxytricha marcili (Ciliophora, Oxytrichidae), was found and characterized as follows: in vivo length about 60-80 mum x 30-40 mum wide; on average 22 adoral membranelles; 18 left marginal cirri; 18 right marginal cirri; and 3 small caudal cirri. All specimens analyzed presented 7 frontal cirri (3 anterior + 4 posterior), 1 buccal cirrus, 4 ventral cirri (3 postoral + 1 pre-transverse), and 5 transverse cirri. Among the species found, some are considered as water quality indicators ranging from alpha-mesosaprobity to polysaprobity and isosaprobity.